Hubungan antara Dukungan Sosial Suami dengan Stres Kerja Wanita Berperan Ganda Karyawan Unit Cold Storage KUD Minatani di Kecamatan Brondong Kabupaten Lamongan - Pitaloka, Diah Ayu (2016)
Stress work in working woman had a role double is a condition often experienced by mother workers, where a person subjected to pressure and is too heavy a price by assignment verb that does not already he finish.Social support of the family particularly the husband is expected to reduce the job stress in women employees unit of cold storage kud minatani. The sample collection technique that is used is purposive random sampling , the number of a subject in this study as many as 123 people .The methods of using the quantitative approach with the scale of a measuring instrument .That is the scale of job stress and scale of social support husband .Engineering the analysis used is the correlation product moment of pearson . The results of the analysis data is collected a correlation coefficient rxy = -0,394 with significance 0,000 p & lt; 0,001 , so that hypothesis advanced by accepted , there was a correlation negative very significant between support social husband with job stress in women work .Contributions effective social support husband with job stress of 15,52 % and 84,48 % influenced other variables .Social support husband are classified as a part medium category with rerata empirical of 63,54 and rerata hipotetik of 60 .The stress working woman had a role double included in a category being with empirical rerata of 76,40 and rerata hipotetik of 75 .